THE IMPACT OF TAX AVOIDANCE, SUSTAINABILITY REPORT DISCLOSURE, AND EARNINGS MANAGEMENT ON FIRM VALUE IN THE DIGITAL ERA WITH CORPORATE GOVERNANCE AS A MODERATING VARIABLES - Endro Andayani (Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2021)
This paper aims to determine whether tax avoidance, sustainability reporting, and earnings management affected firm value. Samples were collected from 80 companies listed on the Indonesian Stock Exchange (BEI)between 2015 and 2019. This research is an explanatory study that employs a quantitative approach and purposive sampling as the sampling technique, using the Absolute Difference Value Method to examine the moderating variable’effect, and SPSS 23 to analyze the data. The finding indicate that while tax avoidance has no negative effect on firm value and Sustainability Report has no positive effect on firm value, earnings management have negative effects on firm value. Corporate Governance did not weaken the effect of tax avoidance on firm value, corporate governance did not strengthen the relationship between sustainability reports and firm value and Corporate Governance weakens the negative effect of earnings management on firm value. This paper contributes to three different strands of research:determinants of tax avoidance in Indonesia for government literature, evaluation, improve, improvement, and performance for companies;for investors, as it is wordthwhile to consider additional factors in order to aid in making an informed assessment of company’s value in this era of technology.